KAJIAN IMBANGAN AIR PULAU BANGKA - Sabri, Fadillah; Hambali, Robi (SIPIL, 2013)
The management of water resources is inseparable from three issues; excessive water in rainy season, lack of water in dry season, and the decreasing quality of water from time to time. The increasing number of residents in one area in turn increases the global need of water, but this need may not immediately be fulfilled. Water balance is a ratio between water need and supply. Water need includes the need for irrigation and non-irrigation water. With the development in Bangka Island, especially the construction of public facilities and infrastructure, trading and industry, agriculture and plantations, the need of water will always increase. It is crucial to know the status of water balance in Bangka Island so that the water resource management can be controlled. The aim of this study is to figure the amount of water needs and water availability in Bangka Island and to determine the status of water balance in Bangka Island using the method of quantitative analysis of ratio between water needs (WN) and water availability (WA). The result shows that Bangka Island water need is 711,75 m3/capita/year. The number of water supply in Bangka Island from 2013 to 2023 shows a surplus in rainy seasons (November-April) and there are deficits in dry seasons (May-October). The condition of water supplies in all areas of Bangka Island is rated good until 2023, except for in Pangkalpinang. The condition of water balance in Pangkalpinang City is bad, which is 388,13% in 2013, 454% in 2018 and 531,04% in 2023.Key Words: Â Water Availability, Water Needs, Water Balance, Bangka Island.